Nail enthesis ultrasound and automated software-guided assessment of bilateral common carotid intima-media thickness in psoriasis and psoriatic arthritis: is there a correlation with clinical and laboratory findings? - José Alexandre Mendonça; Lucas Nogueira Pansani; Mateus Basso Mimoto; Igor Tadeu Garcia Ferreira; Fernanda Bertucci Sanches; Thais de Campos Ferreira Pinto; Vania Aparecida Leandro-Merhi; José Luis Braga de Aquino (BioExcel Publishing Ltd, 2020)
Background: Ultrasound (US) in psoriasis (PsO) and psoriatic arthritis (PsA) is an important tool in several situations to detect joint ecostructural damage as well as other tissue alterations, such as those that occur in the larger vessels. The objective of this study was to detect and correlate the changes that indicate the inflammatory and atherosclerotic process in two groups of patients, using nail US and carotid artery intima-media thickness radiofrequency (RF) software. Methods: A total of 30 patients diagnosed with (PsO) and (PsA) were selected. About 15 patients were present in each group, assigned by the Dermatology and Rheumatology Service of the Universidade Pontifícia Católica de Campinas, São Paulo, Brazil, and were assessed using carotid artery US (radiofrequency quality intima-media thickness [RF-QIMT]), joint US, clinical evaluation, and laboratory tests. Results: Spearman and Pearson correlations between US variables per group were Psoriasis Area and Severity Index (PASI) and loss of the nail pattern trilaminar: r=0.658, p=0.015; Framingham Score (FS) and Internal Resistance Index (IR): 0.351 to 0.526, p=0.034 to 0.002; the significant correlations by the Bayesian factor (BF) were those with a BF greater than 2.5, between QIMT expected with FS: r=0.677, BF=10.06, with total cholesterol: r=0.5232, BF=2.60, and QIMT-RF with low density lipoproteins: r=0.633, BF=3.70. Conclusion: The use of US in the evaluation of these patients showed significant correlations between clinical and laboratory measures, characterized by QIMT and FS as well as changes in nail insertion. Future studies may demonstrate an even better interaction.